2018
DOI: 10.1007/s11886-018-1067-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α in Heart Failure: an Updated Review

Abstract: Purpose of the review Pro-inflammatory cytokines are consistently elevated in congestive heart failure. In the current review, we provide an overview on the current understanding of how Tumor Necrosis Factor-α (TNF-α), a key pro-inflammatory cytokine potentiates heart failure by bringing imbalance and overwhelming the anti-inflammatory responses disrupting the homeostasis maintaining process. Recent finding Studies have shown co-relationship between severity of heart failure and levels of pro-inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 169 publications
(176 reference statements)
2
90
0
9
Order By: Relevance
“…TNF receptors (TNFRSF1A1 and TNFRSF1B) mediate the downstream cellular effects of TNF‐α, a pro‐inflammatory cytokine important for repair following tissue injury. However, persistent up‐regulation of TNF‐α leads to chronic inflammation and is implicated in cardiac dysfunction and HF …”
Section: Discussionmentioning
confidence: 94%
“…TNF receptors (TNFRSF1A1 and TNFRSF1B) mediate the downstream cellular effects of TNF‐α, a pro‐inflammatory cytokine important for repair following tissue injury. However, persistent up‐regulation of TNF‐α leads to chronic inflammation and is implicated in cardiac dysfunction and HF …”
Section: Discussionmentioning
confidence: 94%
“…IL-1α and IL-1β activate a common IL-1 receptor (IL-1R), and seem via inflammation to be involved in a range of pathological processes [34][35][36]. In addition, TNF-α appears to be critical in the onset of pro-inflammatory signalling in silica-induced pathologies [37,38]. In contrast to larger crystalline silica particles that presumably exert their effects via such pro-inflammatory mediators, small SiNPs may translocate across the airway barrier to the systematic circulation, and potentially exert direct effects in secondary organs [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…In response to tissue injury, the heart activates the innate immune system to begin tissue repair mechanisms (Schumacher and Naga Prasad 2018), which are associated with the occurrence of significant increases in the levels of different pro-inflammatory cytokines (Braunwald 1997;Valen 2011;Mann 2015). This increase in pro-inflammatory cytokines aids in the process of cardiac remodeling and it has been suggested that this acute, proinflammatory stage is followed by an anti-inflammatory response to resolve the injury (Ionita et al 2010).…”
Section: Generation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%